Invasion and Dispersal of Biomphalaria Species: Increased Vigilance Needed to Prevent the Introduction and Spread of Schistosomiasis - Habib, Mohamed R.; Lv, Shan; Rollinson, David; Zhou, Xiao-Nong (Frontiers in Medicine, 2021)
Biological invasion is a matter of great concern from both public health and biodiversity perspectives. Some invasive snail species may trigger disease emergence by acting as intermediate hosts. The geographic distribution of Schistosoma mansoni depends on the presence of susceptible species of Biomphalaria freshwater snails that support the parasite's transformation into infective stages. Biomphalaria spp. have shown strong local and global dispersal capacities that may increase due to the global warming phenomenon and increases in the development of agricultural and water projects. Should intermediate hosts become established in new areas then this will create potential transmission foci. Examples of snail invasions that have had an impact on schistosomiasis transmission include the introduction of Biomphalaria tenagophila to Congo and B. glabrata to Egypt. The current spread of B. straminea in China is causing concern and needs to be monitored closely. An understanding of the mode of invasion and distribution of these snails as well as their experimental susceptibility to S. mansoni will predict the potential spread of schistosomiasis. Here we review the invasion patterns of Biomphalaria snails and factors that control their distribution and the impact that invasion may have on intestinal schistosomiasis transmission. In addition, we propose some possible surveillance responses for optimum control strategies and interventions. Whenever possible, swift action should be taken to contain any new occurrence of these intermediate snail hosts.